Analysis of Flavonoid Levels of Enhalus acoroides in Different Coastal Waters in Ambon Island, Indonesia - Prelly MJ Tuapattinaya; Dominggus Rumahlatu (Hasanuddin University, 2019)
Seagrass contains bioactive compounds or secondary metabolites which can be used as potential drugs. This research aims at analyzing the levels of flavonoids of the leaves of seagrass Enhalus acoroides in three different coastal waters. The sampling of seagrass leaves was carried out in three locations in the coastal waters of Ambon Island, namely the coastal waters of Galala, Rutong, and Waai. The levels of flavonoid were identified using microscopic-microchemical methods. The test results of the flavonoid levels were analyzed descriptively. The results of this research showed that samples of seagrass leaves from the coastal waters of Galala, Rutong, and Waai, after added with NaOH, AlCl3, and NH3reagents showed a color change. It means that the samples from the three coastal waters were positive to contain flavonoids. Therefore, the analysis was continued to determine the average levels of flavonoids of E. acoroides. The average levels of flavonoid in the three coastal waters of Galala, Rutong, and Waai were 0.0192%, 0.1475%, and 3.5697% respectively. The environmental conditions and substrate of seagrass E. acoroides in the coastal waters of Rutong and Waai caused higher levels of flavonoids than the levels of flavonoids in the coastal waters of Galala.